SCIENCE LITERACY SKILLS WITH THE UTILIZATION OF STUDENT WORKSHEET LEARNING TOOL BASED ON PROJECT-BASED LEARNING - Tanjung, Yolla Trisrianca (Universitas Negeri Medan, 2024)
This study aims to determine the effect of project-based learning (PJBL) student worksheets against students science literacy abilities on the use of waste and natural materials in class X SMA Swasta Nusantara Lubuk Pakam in the 2023/2024 school year. The research method used is quantitative, in the form of a true experimental design. The research design used was a pretest-posttest control group design. The population in this study was all class X at SMA Swasta Nusantara Lubuk Pakam, with a total of 6 classes. The sampling technique used in this research is class random sampling. The research sample consisted of two classes: X-1, which was the experimental group using PJBL-based LKPD, and X-2, which was the control group using conventional LKPD. This research instrument is a description-based scientific literacy ability test. The results of the calculation of the hypothesis test using the independent sample t-test obtained a sig. (2-tailed) value < 0.05, indicating that the PJBL-based LKPD has a significant effect on students' scientific literacy abilities in the material on the use of waste and natural materials.